The complete chloroplast genome and phylogenetic analysis of Artocarpus champeden - Ying-Feng Niu; Jin Liu (Mitochondrial DNA. Part B. Resources, 2021)
Artocarpus champeden Spreng. is a popular fruit tree, grown in tropical and subtropical regions. Besides food, A. champeden is also a medicinal plant with various medicinal properties. In this study, A. champeden chloroplast genome was sequenced, assembled, and annotated due to its rich information on species evolution and inter-species genetic relationships. The quadripartite structure of A. champeden complete chloroplast genome is 158,568 bp in length and comprises a large single-copy region (LSC) of 88,076 bp, a small single-copy region (SSC) of 19,028 bp, and two inverted repeat regions (IRa and IRb) of 25,732 bp. A total of 131 genes were annotated, including 85 protein-coding genes, 37 tRNA genes, eight rRNA genes, and one pseudogene. Phylogenetic analysis revealed a close relationship between A. champeden and A. heterophyllus. In addition, the study provides abundant genomic information for future phylogenetic studies of A. champeden and the Moraceae family.